The entropic measure transform - WANG, Renjie; HYNDMAN, Cody; KRATSIOS, Anastasis (Canadian journal of statistics, 2020)
We introduce the entropic measure transform (EMT) problem for a general process and prove the existence of a unique optimal measure characterizing the solution. The density process of the optimal measure is characterized using a semimartingale BSDE under general conditions. The EMT is used to reinterpret the conditional entropic risk-measure and to obtain a convenient formula for the conditional expectation of a process that admits an affine representation under a related measure. The EMT is then used to provide a new characterization of defaultable bond prices, forward prices and futures prices when a jump-diffusion drives the asset. The characterization of these pricing problems in terms of the EMT provides economic interpretations as maximizing the returns subject to a penalty for removing financial risk as expressed through the aggregate relative entropy. The EMT is shown to extend the optimal stochastic control characterization of default-free bond prices of Gombani & Runggaldier (2013). These methods are illustrated numerically with an example in the defaultable bond setting. Les auteurs présentent le problème de transformée de mesure entropique (TME) pour un processus général et prouvent l’existence d’une mesure optimale unique caractérisant la solution. Le processus de densité de la mesure optimale est décrit à l’aide d’équations différentielles stochastiques rétrogrades pour une semi-martingale sous des conditions générales. Les auteurs utilisent la TME pour réinterpréter la mesure de risque entropique conditionnelle et obtenir une formule pratique pour l’espérance conditionnelle d’un processus admettant une représentation affine sous une mesure associée. Ils utilisent ensuite la TME pour fournir une nouvelle caractérisation du prix des obligations vulnérables au défaut, des contrats de gré à gré et des contrats à terme lorsqu’un processus de diffusion par sauts gère la valeur des actifs. La définition de ces problèmes d’établissement des prix en fonction de la TME propose une interprétation économique de maximisation du retour sujet à une pénalité retirant le risque financier exprimée par l’entropie relative agrégée. Les auteurs montrent que la TME généralise la caractérisation du contrôle optimal pour le prix des obligations sans défaut de Gombani & Runggaldier (2013). Ils illustrent leur méthode numériquement avec un exemple dans le contexte où des obligations peuvent faire défaut.